(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: The study of the harmful effects of chemicals and substances on the human body and environment is called toxicology, an important branch of medical science. The subject toxicology also deals with features of presentation on the human body and environment along with its methods of detection and treatment. Different toxins and poisonous substances affect differently based on various external and internal factors. Importance of Integration: It is important to teach medical students in undergraduate and postgraduate level toxicology in detail for the effective management of patients. Competency-based medical education has been implemented by the National Medical Commission which mandates integrated teaching of toxicology keeping it aligned with other stakeholder subjects like medicine, pharmacology, biochemistry, and others. Benefits of Integration: This concept of integration is helpful in organizing the teaching matters to interrelate or unify with other subjects taught in separate academic courses or departments. Ultimately it reduces the redundancy. Integrated learning of toxicology includes innovative teaching-learning materials and methods to promote contextual learning for better retention and performance. The correlation of contents between basic and clinical sciences plays a vital role in teaching and learning toxicology